Praktik jual beli di platform E-Commerce: Tinjauan fiqih terhadap akad, transparansi, dan kepatuhan syari’ah di platform shopee, tokopedia, dan sejenisnya - Octavia, Irene Hevy (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has driven massive growth in online sales transactions through various e-commerce platforms such as TikTok Shop, Shopee, Tokopedia, Lazada, and Bukalapak. This study aims to review the suitability of transaction practices on these platforms with Islamic economic principles, particularly through the application of sharia contracts such as salam, wakalah, and ju'alah. From a fiqh muamalah perspective, online transactions are permissible as long as they do not involve elements of gharar (uncertainty), fraud (najasy), or ambiguity regarding the object, price, and delivery time. The findings indicate that while most platforms have made efforts to adopt Sharia principles through secure payment systems, information transparency, and consumer protection features, gaps still exist, such as product ambiguity, COD price rounding, and promotional practices that raise doubts. Therefore, stricter oversight and education for businesses and consumers are needed to ensure that e-commerce transactions align with Sharia principles, fairness, and benefit all parties involved.